Ventricular Hyper-Excitability Revealing Cardiac and Mediastino-Pulmonary Sarcoidosis - Mokhlis, Houda; Bachri, Houda; lemouaden, Rime; Malki, Mohamed; Ahchouch, Sara; Boumaaz, Meryem; Zaimi, Achraf; Loudiyi, Nadia; Mouine, Najat; Asfalou, Ilyasse; et al. (Cardiology and Cardiovascular Medicine, 2022)
Abstract not available in the source database.